2022
DOI: 10.1007/s41669-021-00320-4
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation Supported by Qualitative Data About the Patient Concerns Inventory (PCI) versus Standard Treatment Pathway in the Management of Patients with Head and Neck Cancer

Abstract: Background The head and neck cancer (HNC) Patient Concerns Inventory (PCI) is a condition-specific prompt list that allows patients to raise concerns to cancer consultants that otherwise might be overlooked. Objective This is the first economic evaluation of the PCI in patients with HNC investigating the costs and effects to the health service of not prioritising certain treatment pathways in addition to the primary cancer pathway. Additional costs can be accrued due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Pain was a major dysfunction (63%) as was physical and social-emotional functioning and this group reported many PCI issues, median (IQR) 7 (4–11) 7 Dimelow et al (2021) [ 51 ] A prompt list sent out to the patient in advance of the consultation (Patient Concerns Inventory) could be a useful adjunct in telephone consultations 3, 4 Elaldi et al (2020) [ 18 ] Identification of patient needs and concerns along with multidisciplinary management of persistent symptoms and psychological distress seem essential steps towards improving QoL of HNSCC patients. 6 Ezeofor et al (2022) [ 44 ] The PCI appears to be a low-cost intervention that generates a cost-effective benefit to patients from a UK National Health Service (NHS) perspective if rolled out as part of routine care. Qualitative evidence has shown that the use of the PCI is supported by consultants in routine practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain was a major dysfunction (63%) as was physical and social-emotional functioning and this group reported many PCI issues, median (IQR) 7 (4–11) 7 Dimelow et al (2021) [ 51 ] A prompt list sent out to the patient in advance of the consultation (Patient Concerns Inventory) could be a useful adjunct in telephone consultations 3, 4 Elaldi et al (2020) [ 18 ] Identification of patient needs and concerns along with multidisciplinary management of persistent symptoms and psychological distress seem essential steps towards improving QoL of HNSCC patients. 6 Ezeofor et al (2022) [ 44 ] The PCI appears to be a low-cost intervention that generates a cost-effective benefit to patients from a UK National Health Service (NHS) perspective if rolled out as part of routine care. Qualitative evidence has shown that the use of the PCI is supported by consultants in routine practice.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary exploratory analyses indicated that HRQOL status early after the completion of treatment was the dominant predictor of HRQOL after another 12 months and the trend in analyses over a range of outcomes suggests that patients with worse early HRQOL could benefit more from the PCI–HN. The PCI–HN is a low-cost intervention which generates a cost-effective benefit to patients from an NHS perspective if rolled-out as part of routine care [ 44 ]. The trial findings indicated that a pragmatic multi-unit cluster trial for a study of this nature was feasible, and it has helped increase the profile of this type of approach in clinical care as well as increasing the body of evidence with publications in peer review journals.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first study to investigate the impact of introducing the PCI pre-consultation on specific communication events regarding patient concerns during HNC follow-up consultations. Our previous work has reported the main effects of PCI usage on QoL [ 24 ] and an economic evaluation [ 25 ]. Results of this current study show a significant difference in number of concerns raised between trial groups, where patients in the PCI group raised on average 2.5 more concerns than non-PCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Patient Concerns Inventory-Head and Neck (PCI-HN) is a condition-specific item prompt list, which patients select from before their appointment, to help guide the outpatient consultation, and has been shown in a randomised trial to improve outcomes [52] and be cost-effective [53]. It has been reported to be the most appropriate tool specific to HNC with a particular emphasis on the importance of content validity over quantitative psychometric properties [51].…”
Section: The Patient Concerns Inventory-head and Neckmentioning
confidence: 99%